Towards a school library development policy for Uganda - Magara, Elisam; Nyumba, Joyce Bukirwa (Library review, 2004)
This paper is based on a literature review and aims at providing guidelines for a school library development policy for Uganda. It presents the need for school libraries, describes the background to the policy formulation process, and analyses the existing legal and institutional framework for school libraries in Uganda. The paper highlights the current initiatives in support of school library development in Uganda and gives justification for a school library development policy for Uganda. Guidelines and implementation strategies are given to guide the formulation of this school library development policy.
Keywords: School libraries, Uganda, Design and development